Correlation Between Early Age Pregnancy with Low Body Weight (LBW) Newborn at Universitas Airlangga Academic Hospital, Surabaya, Indonesia - Roy Prasojo Wibowo; Budi Prasetyo; Widati Fatmaningrum; Ahmad Hadi Modi (Biomolecular and Health Science Journal, 2022)
Introduction: Birth weight is often used to evaluate a newborn baby’s health. Low birth weight (LBW) is one of the leading causes of neonatal mortality. Mothers under the age of 20 (early pregnancy) are at a greater risk of affecting the weight and nutritional status of the unborn child. This research aimed to determine the relationship between early pregnancy and LBW. Methods: This was a cross-sectional study of women and newborns at Airlangga University academic hospital from January through December of 2017. Data on characteristics such as maternal age and LBW were collected. The correlation between early pregnancy and infant weight was determined using the Chi-square test, with a significance level of p<0.05. Results: We conducted research on 210 pairs of mothers and their infants. 64 (30.48%) of the pregnancies occurred in women under the age of 20; 61 (29.55%) were born LBW (weighing less than 2,500 grams). Early age pregnancy was linked to a higher proportion of LBW infants (p=0.001). Research indicated that the risk of LBW was more significant in the early groups of pregnancy.Conclusion: This research establishes a relationship between early age pregnancy and LBW. The findings may aid in identifying vulnerable mothers in need of further assistance and personalized treatments.